2012
DOI: 10.1111/j.1439-037x.2012.00525.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Advances in Adapting Rice to a Rapidly Changing Climate

Abstract: Rice, with its wide geographic distribution extending from 50°N to 35°S, is expected to be the most vulnerable cultivated crop to future changing climates. Among the different abiotic stresses, extreme temperatures coinciding with critical developmental stages, increasingly frequent floods and drought spells, and worsening sea water inundation are some of the major threats to sustainable rice productivity. Following the successful implementation of molecular markerassisted backcrossing to introgress large-effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 86 publications
(114 reference statements)
2
61
0
Order By: Relevance
“…This effect was particularly evident in 'F60' rice plants (Figure 4). These observations are in agreement with those of Jagadish et al (2012), who reported that an increased respiration rate is a response of rice plants to high temperatures. Previously, Almeselmani et al (2012) evaluated two wheat cultivars ('PBW343' and 'C306') under elevated daytime temperatures and concluded that 'C306' plants were more tolerant.…”
Section: Discussionsupporting
confidence: 83%
“…This effect was particularly evident in 'F60' rice plants (Figure 4). These observations are in agreement with those of Jagadish et al (2012), who reported that an increased respiration rate is a response of rice plants to high temperatures. Previously, Almeselmani et al (2012) evaluated two wheat cultivars ('PBW343' and 'C306') under elevated daytime temperatures and concluded that 'C306' plants were more tolerant.…”
Section: Discussionsupporting
confidence: 83%
“…However, crop phenology is simultaneously affected by crop management, including cultivar shift and date of sowing, which can also be adjusted to cope with climate variability. In fact, the planting of shorter-duration crops could be an effective means of adapting to climate change, as crops with earlier anthesis or sowing dates can avoid extreme heat stress [44] and be less exposed to drought [45] during the grain-filling period, which consequently benefits yield. Cammarano and Tian [46] found that for each 1 • C increase in air temperature, maize yield decreases on average by 4.6%.…”
Section: Potential Impact On the Irrigation Districtsmentioning
confidence: 99%
“…Such has been the case with aquaculture and rice farming in the Mekong Delta (Vietnam) (Pucher et al, 2013). Furthermore, despite clear advantages for adapting rice to climate change, the use of modern varieties with high tolerance to abiotic stresses such as submergence (Jagadish et al, 2012) also draws responsibilities for habitat management as marginal areas that were once a refuge for wildlife become more feasible for rice production. There is an urgent need for scientists and managers to develop sound strategies for coexistence of rice production, resource extraction activities (aquaculture and fishing) and wildlife conservation, particularly as biodiversity conservation is a major index of sustainable development.…”
Section: Increasing Areas Of Productionmentioning
confidence: 99%